CENTRAL STATE VS REGIONAL AUTONOMY - POLITICAL ELITE’S ACTION STRATEGY - Pavlenishvili, Nino (PEOPLE: International Journal of Social Sciences, 2024)
The role of the autonomous institutions is significant in the elaboration of the specific strategies conducive for the political elite of either regional autonomy or central state to achieve their territorial, political and economic goals. Functional autonomous institutions enable the political elite to mobilize its ethnic group and radicalize demands. Rational assessment of the geographic location, instrumentalization of primordial markers (focus on historical memory) and constructivist ascriptions along with structural situation in and out of both, the autonomy and central state defines contemplated ethnic politics with far-going consequences of the both, central state and autonomy. Autonomy’s political elite activates primordial ascriptions, as well as, constructionist attitudes, considers geographic location to mobilize ethnic followers, press claims for secession and influence central authority to upgrade autonomous status through negotiations or violent confrontation. The Central state political elite’s decision about action strategy selection depends on the structure of situation inside and outside of the country. While operationalizing selected strategy central administration applies primordial and constructivist approaches to impact local authority’s decision- making process. Two autonomous republics of the Russian Federation, Tatarstan and Chechnya, are explored in the first decade after collapse of the Soviet Union to test theoretically identified factors impacting formation of ethnic politics and action strategies in the central state and autonomy. The methods’ triangulation (process-tracing method, discourse analysis of the official document and public speeches and semi-structured interviewing) was utilized to validate the research findings. On its way to upgrade autonomous status, Tatarstan built civic nationalism guaranteeing peaceful coexistence of the ethnic groups. Chechnya’s oppressive historic experience intensified rigid ethnic politics leading to protracted ethnic confrontation.